GATA6 regulates expression of annexin A10 (ANXA10) associated with epithelial–mesenchymal transition of oral squamous cell carcinoma. (December 2022) - Takayama, Shun; Morita, Yoshihiro; Nishimoto, Ayano; Nishimura, Junya; Takebe, Katsuki; Kishimoto, Satoko; Matsumiya-Matsumoto, Yuka; Matsunaga, Kazuhide; Imai, Tomoaki; Uzawa, Narikazu
Abstract: Oral squamous cell carcinoma (OSCC) can disturb oral function and quality of life and is associated with poor survival, likely due to the development of cervical lymph node metastases. Epithelial-mesenchymal transition (EMT) is a process in which cells acquire molecular alterations that facilitate cell motility and invasion, and has been associated with tumor metastasis. EMT changes also play important roles in the induction of lymph node metastasis in OSCC. GATA6 is known as the earliest marker of the primitive endoderm lineages. GATA6 inhibits de-differentiation and EMT in human pancreatic ductal adenocarcinoma cells and promotes EMT. However, in OSCC, the expression and function of GATA6 in EMT and lymph node metastasis remains unclear. Therefore, this study aimed to clarify the targets of GATA6 in OSCC cells and whether the change in GATA6 expression affects EMT in OSCC cells, as well as the association between GATA6 and lymph node metastasis. The results showed that GATA6 knockdown OSCC cells promoted EMT and increased lymph node metastasis compared with control cells, whereas the overexpression of GATA6 inhibited the induction of EMT and reduced lymph node metastasis. In addition, annexin A10 (ANXA10) which is the largest type of Ca 2+ -regulated phospholipid-binding protein in eukaryotic cells was detected as a target gene for GATA6 and ANXA10 suppressed Vimentin expression in EMT in OSCC. Therefore, the GATA6/ANXA10 cascade may be a potential therapeutic approach for the treatment of lymph node metastases in OSCC patients. Highlights: GATA6 is a regulator of the epithelial–mesenchymal transition in oral squamous cell carcinoma. Overexpression of GATA6 significantly suppresses lymph node metastasis in vivo. ANXA10 is identified as a target gene for GATA6 in oral squamous cell carcinoma. ANXA10 is shown to suppress vimentin expression in the epithelial–mesenchymal transition